Influence of Tithonia POC and Nano Bubble Technology on Hydroponic Pakcoy (Brassica rapa L.) Quality - Alqaramah, Rachel; Fevria, Resti; Vauzia, Vauzia; Razak, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hydroponics offers a modern agricultural solution to overcome land limitations in urban settings. Despite its advantages, the system commonly relies on synthetic fertilizers like AB Mix, which are costly and may pose environmental risks. As a sustainable alternative, liquid organic fertilizer (POC) derived from Tithonia diversifolia, combined with nanobubble technology, may improve nutrient uptake efficiency in plants. This study aimed to evaluate the effect of combining AB Mix and nano POC on the growth of pakcoy (Brassica rapa L.) in a nanobubble-based hydroponic system. A Completely Randomized Design (CRD) was used with five treatments and five replicates: P1 (100% AB Mix), P2 (75% AB Mix + 25% nano POC), P3 (50% AB Mix + 50% nano POC), P4 (25% AB Mix + 75% nano POC), and P5 (100% nano POC). The measured variables were plant height, leaf number, leaf area, fresh weight, and dry weight. ANOVA and Duncan’s 5% test showed that P2 resulted in the best growth, while P5 had the lowest. These results indicate that nano POC is effective as a supplementary nutrient but cannot fully replace inorganic fertilizers. Further research is necessary to determine the optimal composition and its influence on plant quality.